Learning Outcomes Associated with the Execution of Short Service in Badminton Among Junior High School Students: The Proficiency of Eye-Hand Coordination in Motor Activities - Sitorus, Akbar Alvian; Simaremare, Aris; Arjuna, Arjuna; Buulolo, Boisandi; Pandia, Brema Pehulisa; Karo Karo, Alan Alfiansyah Putra; Salim, Muhammad Ikram; Sitanggang, Charisma Maranatha; Sihombing, Lasdo Pangihutan; Laia, Yupiter Prakasa (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aimed to investigate the relationship between eye-hand coordination and the learning outcomes associated with badminton short service execution among junior high school students, and to determine the extent to which eye-hand coordination influences skill acquisition in this fundamental badminton technique. Materials and methods: The study employed a quantitative non-experimental approach involving 27 male junior high school students aged 13-15 years from Medan City, Indonesia. Data collection utilized pre-test and post-test measurements of eye-hand coordination through a standardized ball throwing and catching test and short service proficiency using an adapted French Short Service Test. Students participated in an eight-week training program focused on developing eye-hand coordination and short service technique. Data were analyzed using SPSS version 26, employing descriptive statistics, Pearson correlation, and regression analysis. Results: Findings revealed a significant positive correlation between eye-hand coordination scores and short service proficiency (r = 0.783, p < 0.001). Regression analysis indicated that eye-hand coordination accounted for approximately 61.3% of the variance in short service performance. Students with higher initial eye-hand coordination demonstrated greater learning improvements following the training intervention (19.1 ± 5.2 points) compared to students with lower coordination (13.7 ± 4.5 points). Conclusions: Eye-hand coordination significantly influences badminton short service learning outcomes among junior high school students. The development of eye-hand coordination enhances students' ability to perform precise short services, suggesting that physical education curricula should incorporate specific coordination training to optimize badminton skill acquisition.